(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the side effects of ginseng product on human. Study Design: Experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, University of Health Sciences, Lahore from Jan 2005 to December 2007. Materials and Methods: Thirty adult albino mice were split into three groups of 10 mice (eight pregnant females and two males) in each group. Group A received distilled water for full term of gestation. Group B received HTD (780 mg/kg/day) mixed in 0.1ml of distilled water and Group C received MTD (1560/mg/kg/day) mixed in 0.1ml of distilled water for full term of gestation. Embryos were taken by doing C-section on gestational day 18. The fetuses were prospected and kidneys were removed. The kidneys were fixed; processed and microscopic slides were prepared. Results: Histological examination showed signs of renal tubular malformation as well as varying degrees of un-differentiated mesenchymal connective tissue along with congestion and erythrocyte infiltration in the tissue preparations. These alterations were dose dependent in experimental groups. These changes were remarkable in the group C as compared with the group A or group B. Our study shows that Ginseng has embryotoxic consequences and indicates that more researches and close observation of embryotoxic outcomes of Ginsenosides on pregnancy are required. Conclusion: Our investigation indicates that Ginseng products have teratogenic effects in vivo and suggest that further investigations and monitoring of embryonic effects of Ginsenosides on human pregnancy are warranted.